KEARIFAN LOKAL MASYARAKAT PANYALAIAN DALAM TRADISI PERNIKAHAN - Dewi Anggraini (Ensiklopedia Social Review, 2022)
: The research aims to find out the value and meaning in the panyalaian wedding tradition of West Sumatra, the research was conducted in the village of bintungan panyalaian West Sumatra, this research was conducted in December 2018, while the approach taken is a qualitative approach, namely research that emphasizes social and community phenomena. As for the type of descriptive research research. The data sources used are observation, interviews and documentation. The results showed (1) Preparation for the implementation of the marriage that was carried out was not all the processions carried out in accordance with Nagari regulations. (2) Preparations that are carried out are only deliberations with niniakataumamak conducting deliberations with niniak mamak.Keyword : Local wisdom, wedding traditions